Bahasa Ibu Zaman Now Dalam Budaya Komunikasi Antarpribadi - I Gede Titah Pratyaksa (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2018)
Language that serves as a means of interpersonal communication for the people of Bali, because the language of Bali is the mother tongue for the people of Bali. Balinese language is a reflection of all aspects of human life and also as a language of instruction in the social. Balinese language has a position and function that is able to become the identity and identity of Balinese people. As for some functions of the language of Bali is very important for the community, among others, as a symbol of pride of Bali, as a means of communication or liaison in the community, as the identity of the people of Bali. The purpose of this research is to know the Language of Mother Age of Now in Culture of Interpersonal Communication. The results of this study include Mother language (Balinese) today in the culture of interpersonal communication is very useful to know yourself and others. The Balinese language also teaches to better appreciate and maintain good relationships with others. The Balinese language of today is mixed because of foreign terms (as in the field of technology) which is not possible to be replaced using Balinese language.Keywords: Keywords: Mother Language, Today, Culture, Interpersonal Communication